The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/resources10050044
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Criteria Analysis of Smart Cities on the Example of the Polish Cities

Abstract: This paper presents the application of a Multi-Criteria Decision Making (MCDM) method for the ranking of smart cities. During the construction of the MCDM techniques, the importance of the decision-making approach for the linear ordering of 66 Polish cities with powiat status was presented. The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) was used for evaluation. The method has been verified by applying it to measure urban smartness. The TOPSIS method allowed compilation for a fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
0
8
0
1
Order By: Relevance
“…It draws a skilled and talented workforce, which raises the city's allure for businesses and commercial operations. [21,28,29], [13,[30][31][32].…”
Section: Smart Economymentioning
confidence: 99%
See 1 more Smart Citation
“…It draws a skilled and talented workforce, which raises the city's allure for businesses and commercial operations. [21,28,29], [13,[30][31][32].…”
Section: Smart Economymentioning
confidence: 99%
“…This element addresses the human aspect of cities and fosters social cohesion through civic engagement and lowering obstacles to social participation. Its indicators advance social and human capital of the community by enhancing the financial and emotional wellbeing of residents and encouraging a healthy lifestyle [13,21,[28][29][30][31][32].…”
Section: Smart Livingmentioning
confidence: 99%
“…Smart city issues are widely described in the literature (Bashynska & Dyskina, 2018;Bibri & Krogstie, 2017;Albino et al, 2015;Wang & Wu, 2015;Allwinkle & Cruickshank, 2011;Komninos, 2009;Szpilko, 2020;Hajduk, 2021). Researchers have shown that many cities are being developed under the smart city banner (Cugurullo, 2020).…”
Section: Smart City Conceptmentioning
confidence: 99%
“…Continuous data are used to assess the most complex socio-economic phenomena using multicritical methods, the source of which is most often public statistics. However, there are complex phenomena in the evaluation, such as quality of life and quality of service, for which questionnaire surveys and order scales are used [25,26]. One effective way to analyze the quality of life is to use a multi-criteria analysis [27,28].…”
Section: Introductionmentioning
confidence: 99%